Limiting Profit Shifting in a Model with Heterogeneous Firm Productivity - Dominika Langenmayr (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2011)
This paper analyzes measures that limit firms' profit shifting activities in a model that incorporates heterogeneous firm productivity and monopolistic competition. Such measures, e.g. thin capitalization rules, have become increasingly widespread as governments have reacted to growing profit shifting activities of multinational companies. However, besides limiting profit shifting, such rules entail costs. As the regulations can only focus on the means to shift profits, not on profit shifting itself, they impose costs on all firms, no matter whether these firms shift profits abroad or not. In the model, these costs force some firms to exit the market. Thus, as this makes the remaining firms more profitable, regulations to limit profit shifting may even increase the aggregate amount of profits shifted abroad. From a welfare point of view, it may even be optimal no to limit profit shifting at all.
Keywords: H25; H73; F23; 330; profit shifting; heterogeneous firms; tax competition; Multinationales Unternehmen; Gewinnverlagerung; Steuerpolitik; Steuerwirkung; Kosten; Produktivität; Steuerwettbewerb; Theorie